If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(y + 5) = 77 Reorder the terms: 11(5 + y) = 77 (5 * 11 + y * 11) = 77 (55 + 11y) = 77 Solving 55 + 11y = 77 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + -55 + 11y = 77 + -55 Combine like terms: 55 + -55 = 0 0 + 11y = 77 + -55 11y = 77 + -55 Combine like terms: 77 + -55 = 22 11y = 22 Divide each side by '11'. y = 2 Simplifying y = 2
| 12x=x^2+35 | | 60x+40y=2040 | | -m/9=1 | | (X-46)+(x+4)=90 | | 32x+40y=1200 | | 0.2k=-15 | | 30x=9 | | 2a(a-1)(3a-1)=0 | | 80x=-60 | | -7y-4=-3(y-4) | | -t/7=2 | | 12/4*2-7 | | X+156=154 | | 67+x(.25)=85 | | 12/y=3/4 | | g(-1/2)=2(-1/2)-3 | | 3(v-5)=39 | | 6x-15/2x-5 | | 13x-7=11x+3 | | 3(v-5)=9 | | Y-17=-28 | | 12+5x=-2x+61 | | -4r+5r=r | | V-v+4v=4 | | 4/x-3.4=17 | | 4x-9=3forx | | 1/4z=1 | | 3x-4=12-10 | | 15k-14k-1=13 | | 8m+24=-3m+3 | | 25+(x-5)=90 | | 4w-2w=20 |